Effect of caffeine on upper-body anaerobic performance in wrestlers in simulated competition day conditions - Aedma, M.; Timpmann, S.; Ööpik, V. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Peak power (PP) and mean power (MP) attained in upper body sprint performance test are considered important factors for competitive success in wrestling. This study aimed to determine whether acute caffeine ingestion would better maintain PP and MP across a simulated competition day in wrestling. Methods: In a double-blind, counterbalanced, crossover study, 14 trained wrestlers ingested either placebo or 5 mg/kg caffeine and completed four 6-min upper body intermittent sprint performance tests with 30-min recovery periods between consecutive tests. PP and MP were recorded during and blood lactate concentration was measured before and after each test. Ratings of perceived fatigue (RPF) and exertion (RPE) were recorded before and after each test, respectively. Heart rate (HR) was monitored across the whole testing period. Results: Mean power decreased across four tests in both trials (p < .05), but the reduction in PP (from 277.2 ± 34.6 W to 257.3 ± 45.1 W; p < .05) only occurred in caffeine trial. Both pretest blood lactate concentration and HR were higher in caffeine than in placebo trial (p < .05) in the third and fourth tests. No between-trial differences occurred in RPF or RPE. Conclusions: Under simulated competition day conditions mimicking four consecutive wrestling matches, acute caffeine ingestion has a partially detrimental effect on upper body intermittent sprint performance in trained wrestlers. Elevated HR and blood lactate levels observed between tests after caffeine ingestion suggest that caffeine may impair recovery between consecutive maximal efforts.